IDENTIFICATION OF CANDIDA SPECIES IN DIABETIC PATIENTS WITH COATED TONGUE - Hilda Hindasah; Yuti Malinda; Riani Setiadhi; Indah Suasani Wahyuni; Wahyu Hidayat; Nanan Nur’aeny (FKG Unlam, 2019)
Background: Coated tongue is a condition in which the dorsum of the tongue is covered by a white layer containing food debris or microorganisms such as Candida species (Candida spp). Factor that can influence coated tongue including a condition such as Diabetes mellitus which often reduce the production of saliva and initiate the increase of Candida spp in number. Objective: to determine various species of Candida spp. in the saliva of Diabetes mellitus patients with coated tongue as a preliminary condition to detect oral candidiasis. Methods: Coated tongue examination was performed by evaluating the lesion visually or using tongue scraper. Salivary collection was performed using oral rinse concentrate method. Saliva samples were inoculated in Chromogenic Agar to identify Candida spp. by examining the colour and the form of colony. Results: Eight samples (88.8%) were identified as C. albicans while C. parapsilosis was presented in 5 samples (66.6%) and C. tropicalis in 2 samples (22.2%). Overall, C. albicans is the most common Candida spp. that found in oral cavity. Candida spp. as normal flora in the oral cavity could be pathogen if the body's immune system decreases. In this study, there was a slight difference between Candida spp. found in the saliva of Diabetes mellitus patients compared to the control group. Conclusions: Candida spp. that identified in Diabetes mellitus patients with coated tongue are C.albicans, C. glabrata, and C. tropicalis.